Factors Affecting Banking Bailout: A Study on Bangladeshi Commercial Banks - Ahmed, Tanvir; Alam, Mahjabeen Binte; Khan, Zahin Irfan; Hera, Shehrly Mahaboob; Haque, Masnun (Journal of Asian Business Strategy, 2020)
The purpose of this research is to find out the probable causes of private bank's being bailout; on the other hand, it tries to restrain banks to be bailout in proximate future. This research notifies banks about the major issues which they should preferably avoid running their business successfully. The banks are already at the brink of almost facing difficulties relating to operations. A sample of 15 Bangladeshi commercial banks is randomly selected for this quantitative study. The data on the variables are taken from the secondary sources and the financial years ending 2015 to 2018 are considered. The information is analyzed with descriptive statistics, correlation, and regression analysis. The study revealed that the possibility of bailout has a significant association with the size of the bank, the political affiliation of their chairperson and their board size. The loan variable is negatively correlated with the bailout. The amount of loan provided is similar among the banks but the small size banks are suggested to become careful of this amount and provide at a reasonable amount. This study indicates the financial and non-financial variables' effect on bailout. Corporate governance of a bank highly influences the performance of a bank, and the financial stability as well. After a financial turmoil in the world economy, banks could fall in disharmony in their regular operations, which could figment them to be bailout.